Manipulating Surface Termination of Perovskite Manganate for Oxygen Activation. (27th January 2021) - Wang, Xiyang; Li, Xinbo; Chu, Xuefeng; Cao, Rui; Qian, Jingyu; Cong, Yingge; Huang, Keke; Wang, Jiaao; Redshaw, Carl; Sarangi, Ritimukta; Li, Guangshe; Feng, Shouhua
Abstract: For ABO3 perovskite oxides, one of the key issues limiting their utilization in heterogeneous catalysis is the dominant presence of catalytically inactive A‐site cations at the surface. The engineering of B‐site terminated perovskites is considered as an effective method to address this issue, especially when dealing with Mn/Co‐based perovskite catalysts. However, to date, such a strategy has not been fully successful and remains a major challenge in the field. Herein, a Mn‐terminated La0.45 Sr0.45 MnO3 (B‐LSM) is successfully synthesized via a one‐pot hydrothermal method, in which low‐valence Mn ions partially occupy the A site to form the active Mn‐excess phase. Experimental results and theoretical calculations reveal that the presence of the surface Mn termination in B‐LSM optimizes the hybrid orbitals of Mn 3d‐O 2p and promotes the activation of surface lattice oxygen, where the pristine inert lattice O 2− is evolved into active and stable lattice O 2− x . Such structural optimization significantly reduces the activation energy barriers on going from O2 − species to important intermediate O − species during O2 activation. Moreover, this results in good stability and Pt‐like activity for the B‐LSM during CO oxidation. This work offers a new chemical route for the design of advanced perovskite‐type oxides possessing novel functions. Abstract : To address the problem of inert surface AO x segregation in perovskite oxides, high‐efficiency B‐site terminated perovskite manganate is prepared via a one‐pot hydrothermal method, and this improves both activity and durability. This MnO x termination resulting from low‐valent Mn ions occupying an A site facilitates the activation of surface oxygen sites and decreases the activation energy barriers associated with oxygen species.